Verrucous lesion over the foot: a diagnostic challenge - Gosavi, Anil P.; Chavan, Ravindranath B.; Deshmukh, Nitika S.; Khose, Shishir; Kundale, Darshana R.; Raut, Vijay V. (International Journal of Research in Dermatology, 2019)
Infection with Mycobacterium tuberculosis or other very closely related strains, as well as the inflammatory reaction of the host, define the disease tuberculosis. Cutaneous tuberculosis constitutes a small proportion of extrapulmonary tuberculosis. Extensive, multifocal involvement of cutaneous tuberculosis is a rare manifestation. We report one such case of tuberculosis verrucosa cutis in a 24 year old immunocompetent male patient.